Breaking Language Barriers: How Non-Native Entrepreneurs Overcome English Communication Challenges in Global Business - Rita Asminarseh (Universitas Muhammadiyah Makassar, 2025)
This study examines the challenges that non-native English-speaking entrepreneurs face when communicating in global business and explores strategies to overcome these barriers. The main objective is to identify common linguistic and cultural barriers in international entrepreneurship and assess their impact on business success. A mixed-methods approach was used, combining a survey of 150 non-native entrepreneurs and in-depth interviews with 15 experienced business owners. Findings revealed that the most significant challenges included limited vocabulary, difficulties in professional writing (e.g., emails, proposals), and misunderstandings in cross-cultural negotiations. However, proactive strategies such as language training, digital tools (e.g., Grammarly, translation apps), and hiring bilingual staff have proven effective in mitigating these issues. The study concludes that although English proficiency remains a barrier, it can be overcome through targeted learning and adaptive communication techniques. Practical recommendations include integrating business English into entrepreneurship training programs and fostering a mindset for continuous language improvement. These measures can enhance global competitiveness among non-native entrepreneurs.